TG–GC–MS study of volatile products from Shengli lignite pyrolysis. (15th September 2015) - He, Qiongqiong; Wan, Keji; Hoadley, Andrew; Yeasmin, Hasina; Miao, Zhenyong
Highlights: TG–GC–MS was used for the lignite pyrolysis analysis. DTG curve was fitting to 7 sub-curves to analyze the breakage of different bonds. Released gas at different temperatures was identified by GC–MS. Aliphatic and aromatic compounds were classified to understand the pyrolysis process. Abstract: Thermal degradation of Shengli lignite was studied by thermogravimetry coupled with gas chromatography–mass spectrometry (TG–GC–MS) for a temperature range from room temperature to 1200 °C at a heating rate of 5 °C/min. The volatile products released from the lignite gradually with the programmed temperature. The main reaction of pyrolysis took place between 350 °C and 800 °C. Seven sub-curves were used to fit the DTG curve to analyze the breakage of different bonds. More than 100 different substances were identified at different temperatures from the GC–MS results. Alkanes and benzene series were the major constituents of the released volatile products along with alcohol, naphthalene, benzofuran, indane, indole, biphenyl, etc. Most of the aliphatic compounds were released around 430 °C with chain lengths up to C21, with the majority being between C1 and C5. Aromatic hydrocarbons were also released mostly at around 430 °C. The number of substituents in a single aromatic compound was found between 0 and 4. The length of the substituent was C1–C6 (sometimes heteroatom instead) and C1 accounted for the most. Generally, TG–GC–MS results presented the mass loss and released gas information with the programmed temperature to bring a better understanding of the structure of the lignite and the pyrolysis process.